Identificação de fatores críticos de sucesso para monitoramento do nível de satisfação de hóspedes de hotéis - Minciotti, Silvio Augusto (2008)
The current economic moment are facing real wars to get the customers preferences: it is the competition on extremely crowded markets, resulting from several factors, but mainly because of the globalization. This is the reality on several segments, including services, especially on the hotels organizations. It is necessary not only to attend the customer, but to enchant and to surprise them, to make it happen is primordial to know what represents value to them: the items they desire, valorize and are responsible for their decision about what company to choose. This article objective is the identification of critical successful factors and its respective attributes to monitoring the satisfaction level of hotels customers. Considering the available literature about customer's satisfaction in hotels organizations, interviews with specialists, academics and market professionals, it was prepared a questionary which lists the probable items considered as critical success factors and its respective attributes. The application was done with the guests of super luxury hotel located in the city of Campinas. The article also presents the results of this application.